Model Kurikulum Integratif Pesantren Mahasiswa dan UIN Maliki Malang - Husniyatus Salamah Zainiyati (Ulumuna, 2014)
Abstract: Some PTAINs  develop a Ma’had in their campuss. This article is aimed at analyzing the integration of curiculum of UIN Maliki into those of its Ma’had which is called correlated curriculum model. Following this model, students of the Ma’had have to take several steps to complete their study. They have to obtain a certificate of completion of ta‘līm al-afkar al-Islāmī and ta‘lim al-Qur’ān which is required for enrolling in the Islamic studies program and taking comprehensive exam. The Ma’had applies Qur’anic-based learning system. This system maps the concept of science and the religious knowledge, integrates the concept of science and theose of the religious knowledge and elaborates the Qur’anic verses scientifically. The ma’had maintains the tradition of congregational pray, recitation and memorization of the Qur’an and promotes infaq and ╣adaqah. All these are to develop the Islamic culture among the academic community at UIN Malang. Abstrak: Beberapa PTAIN mengembangkan pesantren mahasiswa (Ma’had). Artikel ini mengkaji tentang model pengembangan kurikulum pesantren mahasiswa UIN Maliki Malang. Penulis menemukan bahwa Kurikulum UIN Maliki Malang mengintegrasikan program Ma’had dengan kurikulum UIN Maliki Malang, sertifikat kelulusan ta‘līm al-afkar al-Islāmī dan ta‘lim al-Qur’ān sebagai prasarat untuk memprogram studi keislaman dan sebagai prasarat ujian komprehensif. Ma’had itu menerapkan pembelajaran berparadigma Qur’ani dengan tiga langkah aplikatif, yaitu, (a) memetakan konsep keilmuan umum dan keilmuan agama; (b) memadukan konsep keilmuan umum dan keilmuan agama; (c) mengelaborasi ayat-ayat al-Qur’an yang relevan secara saintifik. Tradisi ma’had seperti salat berjama’ah, khatmil qur’an dan hifd}ul qur’a>n, berinfaq dan sedekah untuk membentuk karakter dan mengembangkan kultur Islami di kalangan civitas akademika.